Aplikasi Perpustakaan Menggunakan Teknologi QR Code Berbasis Android Dengan Metode Prototype (Studi Kasus : SMA PGRI 83 Legok) - Megi Saputra; Ahmad Fikri Zulfikar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In today's world of education, learning media are not only in the classroom, but can also be obtained from the school library. The school library is certainly a very important thing in the world of education where to develop students' knowledge. Currently, in data storage, books and members in the school library are still mostly used manually or by hand. Various problems were found in this manual system, for example library data storage that was not well structured or inefficient, borrowing and returning was still manual. From this problem arises an effective solution for storing book data, library member data, borrowing and returning data. That is by making a library application using Android-based qr code technology by using the prototype method as the identity of books and students and using a database as a data storage area. This application is an application that makes it easier for librarian to store book data and library member data. This library application is made using the Java language. When registering a book, the student librarian (Admin) must fill in the data, where the QR Code can store book data and student data. If the book ID and Student Identification Number are still available, the data will be stored in the database, namely MySQL and PHP as a liaison between the database and android.